A fast-charging/discharging and long-term stable artificial electrode enabled by space charge storage mechanism - Zhao, Linyi; Wang, Tiansheng; Zuo, Fengkai; Ju, Zhengyu; Li, Yuhao; Li, Qiang; Zhu, Yue; Li, Hongsen; Yu, Guihua (Nature communications, 2024)
Lithium‐ion batteries with fast-charging/discharging properties are urgently needed for the mass adoption of electric vehicles. Here, we show that fast charging/discharging, long-term stable and high energy charge-storage properties can be realized in an artificial electrode made from a mixed electronic/ionic conductor material (Fe/Li x M, where M = O, F, S, N) enabled by a space charge principle. Particularly, the Fe/Li 2 O electrode is able to be charged/discharged to 126 mAh g −1 in 6 s at a high current density of up to 50 A g −1 , and it also shows stable cycling performance for 30,000 cycles at a current density of 10 A g −1 , with a mass-loading of ~2.5 mg cm −2 of the electrode materials. This study demonstrates the critical role of the space charge storage mechanism in advancing electrochemical energy storage and provides an unconventional perspective for designing high-performance anode materials for lithium-ion batteries. Lithium-ion batteries with fast-charging properties are urgently needed for wide adoption of electric vehicles. Here, the authors show a fast charging/discharging and long-term stable electrode made from a mixed electronic/ionic conductor material enabled by a space charge mechanism.